Tanggung Jawab Notaris Pengganti dalam Hal Notaris yang Diganti Meninggal Dunia Sebelum Cuti Berakhir - Ni Nyoman Candra Krisnayanti; Ida Ayu Putu Widiati; Ni Gusti Ketut Sri Astiti (Fakultas Hukum, Universitas Warmadewa, 2020)
In a community, the notary public is very important. A notary public contributes to law enforcement in Indonesia. Therefore, the community is very relieved by the existence of a notary public. One of the general professions that can get leave rights is a notary public, butif a notary public is about to take a leave, a substitute notary public must be appoited. If at the same time the notary passed away, a substitute notary is required who will be very important to fill the vacancy of the position. Based on this background, this study was conducted with the aim of outlining the legal status of a substitute notary public in the case of a notary public that is substitutedpassed away before the leave is over and describing the mechanism for completing the administration of a substitute notary protocol if the substituted notary passed away before the leave is over. This research was designed using normative legal research. The results of this study indicated that the legal status of a notary will replace the leadership position of the notary who is on temporary leave, sickness or even death. The substitute notary will carry out the tasks of the notary who is subtituted temporarily or permanently. At that time the notary does not need to be inaugurated based on the provisions of article 35 paragraph 3 UUJN-P. In addition, within not later than 60 days after the death of the replacing notary, the subtitute notary must complete all protocols and make official report on protocol handover, then all protocols are given to the notary who receives the protocol. If the protocol has been approved, it will be signed by a notary, the notary who accepts the protocol, and the regional supervisory board as a temporary official.